Effectiveness of mRNA Vaccines Against COVID-19 Hospitalization by Age and Chronic Medical Conditions Burden Among Immunocompetent US Adults, March-August 2021. (21st December 2021) - Lewis, Nathaniel M; Naioti, Eric A; Self, Wesley H; Ginde, Adit A; Douin, David J; Keipp Talbot, H; Casey, Jonathan D; Mohr, Nicholas M; Zepeski, Anne; Gaglani, Manjusha; Ghamande, Shekhar A; McNeal, Tresa A; et al.
Abstract: Vaccine effectiveness (VE) against COVID-19 hospitalization was evaluated among immunocompetent adults (≥18 years) during March–August 2021 using a case-control design. Among 1669 hospitalized COVID-19 cases (11% fully vaccinated) and 1950 RT-PCR–negative controls (54% fully vaccinated), VE was 96% (95% confidence interval [CI], 93%–98%) among patients with no chronic medical conditions and 83% (95% CI, 76%–88%) among patients with ≥ 3 categories of conditions. VE was similar between those aged 18–64 years versus ≥65 years ( P > .05). VE against severe COVID-19 was very high among adults without chronic conditions and lessened with increasing comorbidity burden.